In-House Bookbinding and Repair - McQueen, Sharon; Twomey, James (Rowman & Littlefield Publishers, 2015)
In-House Bookbinding and Repair is a working document that contains information on setting up both a basic bookbindery and repair lab (i.e. the design, equipment, tools, and supplies needed) and instructions on rebinding and repairing cloth-bound books. Highly illustrated to greater enhance its usefulness, this manual also covers various aspects of book repair and conservation, and contains appendixes on manufacturers and suppliers of materials and products discussed in the text, an extensive Glossary of terms, a separate section on World Wide Web Resources, and a helpful bibliography. This manual has proven valuable to libraries of all sizes and locations. Library managers and administrators will find it a worthwhile resource as they contemplate the utility of an in-house lab. Library staff charged with bookbinding and book repair will find the manual to be a practical reference tool. The volume is also designed to be used as a primer for related courses in Library and Information Science Studies programs and may be of interest to individuals interested in private practice. For this second edition, the 2005 manual has been updated and every chapter significantly revised and/or expanded with a view to greatly increasing the book's practical value. Our revisions reflect decades of bench experience in the workshop. The Bibliography and Internet Resources have been updated. Information on manufacturers, suppliers, and supplies has been revised to reflect changes in the marketplace and successful practices. Conservation bookbinding and repair follows old and well-established traditions. Leaving theory and esoteric debate for others, this revised edition is essential reading if you are ready to roll up your sleeves and get to work.